Path integrals and quantum processes - Swanson, Mark S., 1947- (Academic Press, 1992)
In a clearly written and systematic presentation, Path Integrals and Quantum Processes covers all concepts necessary to understand the path integral approach to calculating transition elements, partition functions, and source functionals. The book, which assumes only a familiarity with quantum mechanics, is ideal for use as a supplemental textbook in quantum mechanics and quantum field theory courses. Graduate and post-graduate students who are unfamiliar with the path integral will also benefit from this contemporary text. Exercise sets are interspersed throughout the text to facilitate self-study. Key Features * Explicates the relationship between the operator and path integral formulations of quantum mechanics and quantum field theory * Provides a systematic and detailed presentation of Grassmann variables * Covers Dirac's method of constraints and the relationship of ghosts, gauge invariance, and gauge conditions in gauge field theory * Includes applications to statistical mechanics, the effective action and potential, and anomaly analysis.